2008
DOI: 10.1186/1471-2148-8-279
|View full text |Cite
|
Sign up to set email alerts
|

The Caenorhabditis globin gene family reveals extensive nematode-specific radiation and diversification

Abstract: BackgroundGlobin isoforms with variant properties and functions have been found in the pseudocoel, body wall and cuticle of various nematode species and even in the eyespots of the insect-parasite Mermis nigrescens. In fact, much higher levels of complexity exist, as shown by recent whole genome analysis studies. In silico analysis of the genome of Caenorhabditis elegans revealed an unexpectedly high number of globin genes featuring a remarkable diversity in gene structure, amino acid sequence and expression p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 49 publications
2
44
0
Order By: Relevance
“…Neuronal activities consume lots of oxygen, and C. elegans globin-like proteins are mainly expressed in these cells (10). Recently, we observed that the glb-13 mutant is not sensitive to hypoxia compared to wildtype worms, and Punc-119::hNgb-Tg worms failed to suppress hypoxic death of embryos, larvae, and adult worms (unpublished data).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Neuronal activities consume lots of oxygen, and C. elegans globin-like proteins are mainly expressed in these cells (10). Recently, we observed that the glb-13 mutant is not sensitive to hypoxia compared to wildtype worms, and Punc-119::hNgb-Tg worms failed to suppress hypoxic death of embryos, larvae, and adult worms (unpublished data).…”
Section: Discussionmentioning
confidence: 88%
“…C. elegans has 302 neuronal cells, which comprise one-third of somatic cells. Interestingly, the globin-like proteins are mainly expressed in neurons of C. elegans (10,11). It was reported that behavioral responses of C. elegans to chemicals and gases are controlled by gene activities that are mostly deployed in neurons (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These GFP reporter assays showed that the globins were expressed in distinct, mostly nonoverlapping sets of cells (Supporting Information Table S2) (9). Most of them were expressed in neuronal cells in the head and tail portions of the body and in the nerve cord.…”
mentioning
confidence: 99%
“…(12). The 33 globins can be aligned to fit the globin fold, but additional N-terminal, C-terminal, and interhelical loops create a wide structural diversity among them (Supporting Information Table S1, (9)). Because of these additional aa, the total globin length ranges from 158 aa (GLB-25) to 542 aa (GLB-33).…”
mentioning
confidence: 99%